After Serrano Ethics, Theology and the Law of Blasphemy - M. Casey; A. Fischer; H. Ramsay (Law Text Culture, 2000)
In the latest academic apologia for the antics of bad boy photographer Andres Serrano, Damien Casey attempts to portray him as not only a great liberal artist, but as a great Christian theologian too. One suspects Serrano is laughing up his sleeve at the ease with which such 'postmodern' thinking can be grafted on to the support of his iconoclasm. Casey rehearses some of the standard liberal excuses -- though with no fresh argument -- and then settles down to some more novel points concerning theology, Scripture and society. We will give some treatment of his standard liberal case first, then turn to Casey's more original contributions, and finally comment on the current state of the law regarding this issue.